THE EFFECT OF PROMOTION ON THE INTERESTS OF SALIC PAYING ZAKAT, INFAQ AND SHADAQAH IN AMIL ZAKAT INFAQ AND SHADAQAH JAGAD 'ALIMUSSIRRY INSTITUTIONS - Arilia, Linawati (http://jagadalimussirry.com/, 2020)
Indonesia is the fourth most populous country in the world with a population of 265 million. there are 17 LAZ at national level, 7 LAZ at provincial level and 11 LAZ at district level, the data is LAZ registered at baznas.go.id. The national zakat potential reaches Rp 217 trillion expected to be able to overcome the problem of poverty found in Indonesia . promotion factors become the most important means to attract and retain members. One of the promotional objectives of the amil zakat institution is to inform all types of products offered and try to attract new members. This study is a quasi-experimental study, researchers do not have the flexibility to manipulate subjects. The research design used in this study was